Knockdown of AKR1C3 Promoted Sorafenib Sensitivity Through Inhibiting the Phosphorylation of AKT in Hepatocellular Carcinoma - Zheng, Jia; Yang, Zhihong; Li, Yanlei; Yang, Li; Yao, Ruili (Frontiers in Oncology, 2022)
Background Sorafenib, which can induce ferroptosis, is a multikinase inhibitor for enhancing survival in advanced hepatocellular carcinoma (HCC). However, a considerable challenge for the treatment of HCC is sorafenib resistance. Therefore, targeting the relationship between sorafenib resistance and ferroptosis genes may provide a novel approach for the treatment of HCC. Materials and Methods We analyzed the gene expression and clinicopathological factors from The Cancer Genome Atlas Liver Hepatocellular Carcinoma (TCGA-LIHC), International Cancer Genome Consortium (ICGC), and Gene Expression Omnibus (GEO) databases (GSE109211/GSE62813). The statistical analysis was conducted in R. Cell proliferation was assayed by MTT, cell colony-forming assay, and wound healing assay. Immunofluorescence assay and Western blot were used to evaluate the expression of AKT. Results Many ferroptosis-related genes were upregulated in the sorafenib-resistant group. Aldo-keto reductase 1C3 (AKR1C3) was highly expressed in sorafenib-resistant patients, and the high expression of AKR1C3 was associated with the poor prognosis of patients from the TCGA and ICGC databases. MTT and colony-forming assays showing AKR1C3 overexpression enhanced the proliferation of HCC cells and acute sorafenib resistance. Knockdown of AKR1C3 inhibited the proliferation of HCC cells and increased the drug sensitivity of sorafenib. Immunofluorescence assay and Western blot proved that AKR1C3 promoted the phosphorylation of AKT. Conclusion AKR1C3 can induce sorafenib resistance through promoting the phosphorylation of AKT in HCC. AKR1C3 inhibitors may be used in conjunction with sorafenib to become a better therapeutic target for HCC.